Magnetospheric response and reconfiguration times following IMF By reversals. Issue 1 (21st January 2017) - Tenfjord, P.; Østgaard, N.; Strangeway, R.; Haaland, S.; Snekvik, K.; Laundal, K. M.; Reistad, J. P.; Milan, S. E.
Abstract: The interaction between the interplanetary magnetic field (IMF) and the geomagnetic field at the dayside magnetopause leads to transfer of momentum and energy which changes the magnetospheric configuration, but only after a certain time. In this study we quantify this time, to advance our understanding of the causes for the delayed response of the magnetosphere. We study the response and reconfiguration time of the inner magnetosphere to IMF B y reversals. A superposed epoch analysis of magnetic field measurements from four Geostationary Operational Environmental Satellite spacecraft at different local times both for negative to positive IMF B y reversals and for positive to negative reversals is presented. The magnetospheric response time at geosynchronous orbit to the sudden change of IMF B y is less than 15 (∼10) min from the bow shock (magnetopause) arrival time, while the reconfiguration time is less than 46 (∼41) min. These results are consistent with a B y component induced on closed magnetic field lines due to the asymmetric loading of flux following asymmetric dayside reconnection when IMF B y ≠0. Our results also confirm our earlier studies that nightside reconnection is not required for generating a B y component on closed field lines. Key Points: The magnetosphere responds to a change in IMF B y in less than 15 min in all local times from the presumed arrival at the bow shock At geosynchronous distances, the reconfiguration time is less than 45 min in all local time sectors The reconfiguration time and magnitude of the induced B y component depend on the solar wind velocity